Bioactive Molecule from Streptomyces sp. Mitigates MDR Klebsiella pneumoniae in Zebrafish Infection Model - Cheepurupalli, Lalitha; Raman, Thiagarajan; Rathore, Sudarshan S.; Ramakrishnan, Jayapradha (Frontiers in Microbiology, 2017)
The emergence and spread of multi drug resistant especially carbapenem resistant Klebsiella pneumoniae is a major emerging threat to public health, leading to excess in mortality rate as high as 50–86%. Multi drug resistant K. pneumoniae manifests all broad mechanisms of drug resistance, hence development of new drugs to treat multidrug resistant K. pneumoniae infection has become a more relevant question in the scientific community. In the present study a potential Streptomyces sp. ASK2 was isolated from rhizosphere soil of medicinal plant. The multistep HPLC purification identified the active principle exhibiting antagonistic activity against MDR K. pneumoniae. The purified compound was found to be an aromatic compound with aliphatic side chain molecule having a molecular weight of 444.43 Da. FT-IR showed the presence of OH and C=O as functional groups. The bioactive compound was further evaluated for drug induced toxicity and efficacy in adult zebrafish infection model. As this is the first study on K. pneumoniae – zebrafish model, the infectious doses to manifest sub-clinical and clinical infection were optimized. Furthermore, the virulence of K. pneumoniae in planktonic and biofilm state were studied in zebrafish. The MTT assay of ex vivo culture of zebrafish liver reveals non-toxic nature of the proposed ASK2 compound at an effective dose. Moreover, significant increase in survival rate of infected zebrafish suggests that ASK2 compound from a new strain of Streptomyces sp.was potent in mitigating MDR K. pneumoniae infection.